Nilai-nilai Pendidikan dalam Kisah Yusuf : Penafsiran H.M. Quraish Shihab atas Surah Yusuf - Ismatullah, A.M (Dinamika Ilmu, 2012)
This paper aims to explore the educational values embodied in the story of Yusuf and its relevance in the present life by virtue of the interpretation of the story of yusuf Quraish Shihab al-Misbah in interpretation. From the research results can be concluded that the educational values embodied in the story of Yusuf and its relevance in the present life of them: first, an attitude of openness and communication is established between the child and the father is between Yusuf and Ya'qub, secondly, the wisdom of the head of the family; the third, King fair / Upholding justice, this can be seen in paragraph 43 letter to Joseph, who hinted that the head of state or the king of Egypt at that time to be fair and not arbitrary; Fourth, demand for office / professional. This can be reflected in the letter of Yusuf verse 55 "Yusuf says : Let me state treasurer (Egypt) because actually I was the smart guard, more knowledgeable. And fifth, yusuf patience in the face and pass the trials that befall him.